The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.2307/3586356
|View full text |Cite
|
Sign up to set email alerts
|

The Learning Style Preferences of ESL Students

Abstract: Following a review of the literature on learning styles and cognitive styles for both native speakers (NSS) and nonnative speakers (NNSS) of English, this article presents the results of a questionnaire that asked 1,388 students to identif y their perceptual learning style preferences. Statistical analyses of the questionnaires indicated that NNS learning style preferences often differ significantly from those of NSS; that ESL students from different language backgrounds sometimes differ from one another in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
670
14
68

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 686 publications
(785 citation statements)
references
References 63 publications
(57 reference statements)
33
670
14
68
Order By: Relevance
“…This variation in learning style preferences is supported by the findings of Dorsey & Pierson (1984) and Gardner (1987), who state that younger people are usually active learners while older ones are mainly reflective and abstract. Other studies of the same nature confirm this alteration (Mickler & Zipper, 1987;Reid, 1987;Miglietti & Strange, 2002;Bista, 2008;Ventura, 2010;Tuan, 2011;Karthigeyan & Nirmala, 2013;Major, 2014). In this context, Tuan (2011) argues that "learning styles vary with age" (p. 315); and Dunn and Griggs (1998) claim that the auditory and visual abilities of people in older age tend to become stronger.…”
Section: Discussionsupporting
confidence: 61%
“…This variation in learning style preferences is supported by the findings of Dorsey & Pierson (1984) and Gardner (1987), who state that younger people are usually active learners while older ones are mainly reflective and abstract. Other studies of the same nature confirm this alteration (Mickler & Zipper, 1987;Reid, 1987;Miglietti & Strange, 2002;Bista, 2008;Ventura, 2010;Tuan, 2011;Karthigeyan & Nirmala, 2013;Major, 2014). In this context, Tuan (2011) argues that "learning styles vary with age" (p. 315); and Dunn and Griggs (1998) claim that the auditory and visual abilities of people in older age tend to become stronger.…”
Section: Discussionsupporting
confidence: 61%
“…That is, it sought to find if there is a relationship between the learner's preferences in learning a language (visual, auditory, and kinetic) which is proposed by Reid (1987) and the strategies used by learners which were mainly based on Oxford (1990 a) that was enriched by ideas from Green and Oxford (1995), and Khaldie (2000) which consisted of strategies including memory, cognitive, compensation, metacognitive, affective, and social.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…According to Decapua and Wintergerst [30], Chinese and Vietnamese speakers preferred visual learning, while Reid [31] found that Spanish speakers preferred kinaesthetic and tactile LS. Dorsey and Pierson [32] conclude that age and prior work experience influence LS, and their data indicate that the adults, especially after the age of 33, learn better by doing (kinaesthetic learning).…”
Section: Literature Review On Learning Stylesmentioning
confidence: 99%